1982
DOI: 10.1177/30.3.7061824
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage calcification: an ultrastructural, histochemical, and analytical x-ray microprobe study of the zone of calcification in the normal avian epiphyseal growth plate.

Abstract: Sections from the zone of calcification of ruthenium red-fixed normal avian epiphyseal growth plates were analyzed by various morphological (histochemical) and analytical techniques. Calcium and phosphorus were identified in the chondrocyte pericellular rim, the uncalcified extracellular (territorial) matrix, and in both the peripheral and central aspects of the calcified accumulations within extracellular matrix. Cartilage proteoglycan, as determined by ruthenium binding, positive staining with acidic phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The acidity of crystal ghosts is confirmed under the electron microscope, which shows that they react with ruthenium red, ruthenium hexamine trichloride, therbium chloride, colloidal iron, or bismuth nitrate (Smith 1970;Davis et al 1982b;. Decalcified calcification nodules in the epiphyseal cartilage are, in fact, basophilic under the light microscope, and are stained by histochemical methods for glycoproteins (PAS method) and acid glycosaminoglycans (alcian blue, colloidal iron, ruthenium red).…”
Section: Organic-inorganic Relationships In Cartilagementioning
confidence: 97%
“…The acidity of crystal ghosts is confirmed under the electron microscope, which shows that they react with ruthenium red, ruthenium hexamine trichloride, therbium chloride, colloidal iron, or bismuth nitrate (Smith 1970;Davis et al 1982b;. Decalcified calcification nodules in the epiphyseal cartilage are, in fact, basophilic under the light microscope, and are stained by histochemical methods for glycoproteins (PAS method) and acid glycosaminoglycans (alcian blue, colloidal iron, ruthenium red).…”
Section: Organic-inorganic Relationships In Cartilagementioning
confidence: 97%
“…These results point to crystal ghosts in cartilage as pertaining to, or deriving from, acid proteoglycans, a conclusion strengthened by the observation that they react with CS-56, an antibody specific to the glycosaminoglycan portion of chondroitin sulfate [54]. Results reported by Appleton [55] and Davis et al [56] also point to cartilage crystal ghosts as protein-carbohydrate complexes. Studies of early mantle dentin with soybean agglutinin-gold complexes [36] and with cetylpyridinium chloride-glutaraldehyde as a fixative [57] have shown filament- and needle-like structures similar to crystal ghosts reacting as proteoglycans.…”
Section: Introductionmentioning
confidence: 83%
“…As discussed above, a second, often neglected phase appears to follow, leading to the “maturation” of the crystals and to the removal of all crystal ghosts. This is documented by the fact that crystal ghosts become unrecognizable under the electron microscope as the degree of calcification rises: they do, in fact, gradually disappear from the central zone of the calcification nodules, where the calcification process is completed and is at its highest, final degree, and only remain recognizable at the periphery of the nodules, where the formation of crystals continues (Figure 6; see also [56]). At the same time, the Ca/P ratio increases in the central area of the nodules, and the electron diffractograms acquire the reflections and characteristics of poorly crystalline hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…Davis, et al (1982)2) have suggested that proteoglycans are retained at sites of biologic calcification and that these polyanionic macromolecules may be involved in extracellular calcium translocation . It is also suggested by Pita, et al (1981)10) that this physiological mineralization possibly depends on some active organic structure which is synthesized locally and then phosphorylated and/or binds the calcium.…”
Section: Methodsmentioning
confidence: 99%